Management of children and adolescents with bronchiectasis: summary of the ERS clinical practice guideline - Anne B. Chang (European Respiratory Society, 2021)
Bronchiectasis, characterised by chronic wet/productive cough with recurrent respiratory exacerbations and abnormal bronchial dilatation on computed tomography scans, remains an increasingly recognised but often neglected chronic pulmonary disorder in children and adolescents. An early diagnosis combined with optimal management offers the prospect, at least in some patients, of curing a condition previously considered irreversible. However, unlike in adults, until now no international paediatric guidelines existed. The recently published European Respiratory Society clinical practice guidelines for the management of children and adolescents with bronchiectasis attempts to address this clinical information gap. The guidelines were formulated by panel members comprised of experts from several relevant health fields, the European Lung Foundation and parents of children with bronchiectasis. Systematic reviews and the GRADE (Grading of Recommendations, Assessment, Development and Evaluation) approach guided the nature and strength of recommendations. The recommendations are grouped into clinically relevant topics: diagnosis, evaluating for underlying causes, defining exacerbations, management, systematic care, monitoring, reversibility and prevention. The guidelines seek to achieve: 1) optimal lung growth, 2) preserved lung function, 3) enhanced quality of life, 4) minimal exacerbations, 5) few or no complications, and 6) if possible, reversal of lung injury for each child/adolescent with bronchiectasis. This review presents example cases that highlight the recommendations of the clinical practice guidelines. Educational aims This article is intended for those involved in caring for children/adolescents with bronchiectasis. It aims to inform: Clinicians of the European Respiratory Society recommendations for the diagnosis and management of children/adolescents with bronchiectasis. Adolescents and parents of children/adolescents with bronchiectasis of these recommendations, so as to assist discussions with healthcare teams and help facilitate access to appropriate care.